2014
DOI: 10.1186/1472-6920-14-188
|View full text |Cite
|
Sign up to set email alerts
|

The effect of medical students’ gender, ethnicity and attitude towards poetry-reading on the evaluation of a required, clinically-integrated poetry- based educational intervention

Abstract: BackgroundArt -based interventions are widely used in medical education. However, data on the potential effects of art-based interventions on medical students have been limited to small qualitative studies on students’ evaluation of elective programs, and thus their findings may be difficult to generalize. The goal of this study is to examine, in an unselected students’ population, the effect of students’ gender, ethnicity and attitude towards poetry on their evaluation of a clinically-integrated poetry-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…However, our study suggests that an extensive program that included exposure to ethical issues, communication skills, and humanities studies, had a sustained effect on empathy during the following year in women, but not in men. These findings add to reports on enhancement of empathy in medical students [22][23][24][25].…”
Section: Discussionsupporting
confidence: 80%
“…However, our study suggests that an extensive program that included exposure to ethical issues, communication skills, and humanities studies, had a sustained effect on empathy during the following year in women, but not in men. These findings add to reports on enhancement of empathy in medical students [22][23][24][25].…”
Section: Discussionsupporting
confidence: 80%
“…[14] Poems lend themselves well to an ideal integrated platform that can be used to establish a connect between empathy, clinical, psychological, and factual aspects or to a focused discussion on a single aspect of a subject. [61315]…”
Section: Discussionmentioning
confidence: 99%
“…[4] These tasks not only enable students to understand some of the varied real life applications of classroom teaching but also act as a reinforcer to establish a new memory circuit. [567]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Educational interventions have been suggested to prevent empathy decline during medical studies (18)(19)(20)(21)(22)(23). Previous studies have reported on higher empathy in women as compared to men, following such educational interventions [22,23].…”
Section: Introductionmentioning
confidence: 99%